Acceptance and commitment therapy for individuals having attention deficit hyperactivity disorder (ADHD): a scoping review - Munawar, Khadeeja; Choudhry, Riaz Fahad; Lee, Sook Huey; Siau, Ching Sin; Mohd Kadri, Nursyuhaidah; Sulong, Rose Manisah (Elsevier, 2021)
Objectives